Glycemic index analysis of black rice and redbean based snack bar - Harentya Ayunandha; Mira Sofyaningsih; Debby Endayani Safitri (UHAMKA PRESS, 2021)
Consumption of snacks with high sugar and low fiber content can cause degenerative diseases at a young age. The purpose of this study was to formulate black rice which was converted into brood and red beans in the form of a snack bar that has a low glycemic index. This study used a completely randomized design with one red bean substitution treatment factor with levels of F0 (0%), F1 (10%), F2 (20%) and F3 (30%). The determination of the best snack bar uses an organoleptic test with semi-trained panelists and a food glycemic index test using the iAUC method. The results showed that the 30 g serving weight of the snack bar contained 140 kcal of energy, 4 g of fat, 2 g of protein, 22 g of carbohydrates, and 2 g of dietary fiber. In addition, the black rice and red bean snack bar has a glycemic index of 35.91% and a glycemic load of 7.9 which is included in the low category. Based on the blood glucose response curve, it shows that the snack bar of black rice and red beans causes glucose levels to tend to be stable and hypoglycemia after 2 hours of blood glucose sampling.